Does Self-Esteem Affect Stress Levels in Final Year Medical Students? (A Study In Final Year Medical Students, Faculty Of Medicine, Diponegoro University) - Felita, Fiona; Adiwijaya, Janice Nathania; Hadiati, Titis; Fitrikasari, Alifiati; Savitri, Soesmeyka (Diponegoro International Medical Journal, 2024)
Background: During young adulthood, individuals are forced to encounter countless and overwhelming challenges and responsibilities. Individuals are very prone during this period due to the fluctuation in self-esteem. Low self-esteem might significantly impact individuals as they could perceive challenges as distress, putting them at an increased risk of harming physical or mental health.Objective: To examine the relationship between self-esteem and stress levels among final year medical students, Faculty of Medicine, Diponegoro University.  Methods: This research is an observational analytic correlational study with a cross-sectional design. Samples were obtained by total sampling method involving final year medical students, Faculty of Medicine, Diponegoro University (Class of 2018). Self-esteem was measured using the Rosenberg Self-esteem Scale (RSES), and stress levels were measured using the Perceived Stress Scale (PSS-10) that had been tested valid and reliable. Data were analyzed using Spearman and Lambda Correlation Tests.Results: There were 226 subjects involved in this research. Most subjects had high self-esteem (69,5%) and moderate level of stress (67,3%). Demographic factors (gender, residency status, academic achievement and economic status) were not significantly associated with self-esteem and stress levels. However, there was a significant relationship (p=0.000) between self-esteem and stress levels with moderate negative correlation (r=-0.385).Conclusion: There was a significant relationship between self-esteem and stress levels.